The Use of Cannabis as a Predictor of Early Onset of Bipolar Disorder and Suicide Attempts - Rafaela Torres Portugal Leite; Sarah de Oliveira Nogueira; João Paulo Rodrigues do Nascimento; Laisa Soares de Lima; Taís Bastos da Nóbrega; Mariana da Silva Virgínio; Lucas Monte da Costa Moreno; Bruno Henrique Barbosa Sampaio; Fábio Gomes de Matos e Souza (Neural Plasticity)
Introduction. Bipolar disorder (BD) implies risk of suicide. The age at onset (AAO) of BD carries prognostic significance. Substance abuse may precede the onset of BD and cannabis is the most common illicit drug used. The main goal of this study is to review the association of cannabis use as a risk factor for early onset of BD and for suicide attempts. Materials and Methods. PubMed database was searched for articles using key words “bipolar disorder,” “suicide attempts,” “cannabis,” “marijuana,” “early age at onset,” and “early onset.” Results. The following percentages in bipolar patients were found: suicide attempts 3.6–42%; suicide attempts and substance use 5–60%; suicide attempts and cannabis use 15–42%. An early AAO was associated with cannabis misuse. The mean age of the first manic episode in individuals with and without BD and cannabis use disorder (CUD) was 19.5 and 25.1 years, respectively. The first depressive episode was at 18.5 and 24.4 years, respectively. Individuals misusing cannabis showed increased risk of suicide. Discussion. Cannabis use is associated with increased risk of suicide attempts and with early AAO. However, the effect of cannabis at the AAO and suicide attempts is not clear.